Metodyki zarządzania projektami - Wąsowicz, Marek (Project management methods, 2005)
The author made a comparison of the two most popular Project Management Methods PRINCE2 and PMI. It was described the basic similarities and differences between them. This article includes also many hints for the companies in order to help them in the process of selecting and adapting existing Project Management Methods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 378-383